Inventarisasi Tumbuhan Famili Cactaceae Di Kawasan Wisata Kebun Raya Bogor (International Forum of Researchers and Lecturers, 2023)
Bogor Botanical Gardens is an area that contains various types of plants and is used for conservation, nature tourism, education, research, and so on, including the presence of cactus plants of the Cactaceae family. Cacti are plants that are commonly found in deserts or dry areas. However, cacti also have the ability to survive for a long time without much water. The purpose of this research is to provide information related to the plant species in the Cactaceae family found in the Bogor Botanical Gardens area through an inventory using direct observations of both the morphology and anatomy in a qualitative form. The results of the Cactaceae family plants found include 4 species of the genus Cereus, 1 species of the genus Lophocereus, and 5 species of the genus Opuntia, making a total of 10 species found, namely Cereus hexagonus, Candle Cactus, Mandacaru, Peruvian Apple Cactus, Mexican Fence Post Cactus, Barrel Cactus, Fishhook Cactus, Wheel Cactus, Tephrocactus molinensis, and Prickly Pear Cactus. These three discovered genus have their own distinguishing characteristics.